Analisis Kebutuhan Desain Modul Digital untuk Meningkatkan Digital Skill dan Self-Efficacy Guru Sekolah Dasar - Hidayat, Syarip; Elan, Elan; Saepudin, Saepudin (Universitas Negeri Padang, 2025)
This study aims to analyze the needs of elementary school teachers as the basis for developing a peer tutor-based digital module to improve their digital skills and self-efficacy. The background of this research is the limited ability of teachers to utilize digital technology in learning and their low self-confidence in using technology. This research was conducted at SD Negeri Ciranca, Tasikmalaya, using a qualitative approach with needs analysis methods. Data were collected through interviews, observation, and documentation, and analyzed thematically. The results showed that teachers’ digital skills were in the poor to moderate category. Teachers felt less confident in integrating technology into learning and solving technical problems, although they had good motivation to improve their digital competence. Teachers also showed a very high need for a practical, accessible, and interactive peer tutor-based digital module. The results of this analysis serve as an important foundation for designing a digital module that is responsive to teachers’ needs in supporting the strengthening of their digital skills and self-efficacy. This research is expected to contribute to the development of science and technology in the field of education, especially in preparing collaboration-based professional development modules for teachers. Keywords: needs analysis, digital skills, peer tutor, digital module